Canadian content : culture and the quest for nationhood - Edwardson, Ryan, 1974- (University of Toronto Press, 2008)
Canadian Content looks at Canada as an ongoing postcolonial process of not one but a series of radically different nationhoods, each with its own valued but tentative set of cultural criteria for orchestrating and implementing a Canadian national experience.
Keywords: Canada -- Cultural policy -- History -- 20th century.; Nationalism -- Canada -- History -- 20th century.; Cultural industries -- Government policy -- Canada -- History -- 20th century.; Cultural industries -- Canada -- History -- 20th century.; Canada -- Politique culturelle -- Histoire -- 20e siècle.; Nationalisme -- Canada -- Histoire -- 20e siècle.; Industries culturelles -- Politique gouvernementale -- Canada -- Histoire -- 20e siècle.; Industries culturelles -- Canada -- Histoire -- 20e siècle.; HISTORY -- Canada -- General.; HISTORY -- Canada -- Post-Confederation (1867- ); Cultural industries; Cultural policy; Nationalism; Canada; 1900-1999; History